Development of an innovative THM fully coupled three-dimensional finite element program and its applications - Ziqi Liu; Xiaohui Cheng; Jie Xiao (Underground Space)
A thermal–hydraulic-mechanical (THM) field coupling three-dimensional (3D) finite element (FE) program is developed for complex THM coupled problems in engineering practice. This 3D program incorporates a thermo-mechanical coupled constitutive model known as Tsinghua-Thermo-Soil. The program solves the hydraulic and mechanical fields together and the thermal field separately (i.e., the T-HM scheme). Validation is done against the analytical solutions of one-dimensional (1D) steady-state forced convection-conduction and 1D thermo-elastic consolidation processes. Additionally, effects of the dynamic viscosity coefficient and thermal expansion coefficient of water are analyzed for 1D thermo-elastic consolidation coupled problem. It is revealed that for soils in long-term consolidation and under high loading levels, convective effect is significant and the temperature distribution differs from that obtained by considering only heat conduction. A coupled THM problem of foundations involving an actual engineering energy raft is analyzed. The response of a linear elastic foundation under the combined effect of assumed long-term cyclic thermal loading and mechanical loading process is studied. The results demonstrate that heating leads to the locally accumulation of excess pore pressure and reduces settlement and differential settlement, while cooling has the opposite effects. Due to the heat injected into the foundation exceeding the heat extracted, the ground temperature within several meters of burial depth gradually increases over time, meanwhile the average differential settlement decreases.